Analisis Hukum Islam Terhadap Praktik Jual Beli Padi Dengan Sistem Tebas (Studi Kasus Desa Mlaten Kecamatan MijenKabupaten Demak Tahun 2015/2016) - Shofa, Aizza Alya; , Dr. Imron Rosyadi, M.Ag (2016)
In economic development at present, many buying and selling practices emerge. One of them was a rice trading by using tebas system prevailed in Mlaten Village. Procedure of the tebas system in rice trading was as follow: a farmer makes transaction with a buyer when his rice plants look ripe but they are not ready to harvest, and then, the buyer pays down payment as a booking fee. So, after the transaction, the buyer is not harvesting the rice plants, he must wait for the rice plants are really ready to harvest. And after the buyer harvests the rice plants, he will pay them in full to the farmer. Purpose of the research is to know analysis from Islamic law perspective on the tebas system in rice trading occurred in Mlaten village, Kecamatan Mijen, Demak Regency. Is the tebas system conforming to muamalah requirements in Islamic law? The research is field research with descriptive approach, namely the research aims to find any conformity between Islamic dalil and tebas system in rice trading in Mlaten village so that it may produce intended law. Data of the research was collected by using interview, documentation and observation. The data was, then, analyzed by using descriptive analysis, namely the analysis describes a situation or a phenomenon with words or sentences, and then a conclusion is drawn. Based on the research, results were as follow: the rice trading practice with tebas system in Mlaten village was legitimate according to Islamic law-based analysis, because it conformed to essential principles and trading requirements of Islamic law, namely Aqidain, Ma'qūd 'alaih and sighat (ijab qabul) and being avoided from fasad possibilities such as gharar, riba, and it was one transaction with two intends, to use and to maintain soil by the buyer.